TRANSFORMATION OF SOCIAL SYSTEM IN WORLD OUTLOOK PARADIGM OF MODERNITY: RISKS AND DANGERS - Куцепал, Світлана Вікторівна (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2017)
The article analyzes social transformations of the XXI century caused by globalization, informatization and introduction of the global neoliberal model of the economy. The history of formation of the independent Ukrainian state is characterized with numerous ordeals and tragedies; the genesis of the Ukrainian statehood is a nonlinear, unpredictable and, accordingly, almost unforeseeable process. One can consider that its consequence is ‘chronic’ instability of the domestic social system, ‘impending doom’ of a large part of the public forced to exist ‘on the verge’ when they have to balance between ‘what is bad’ and ‘what is worse’. Accordingly, short intervals of temporary stability are perceived with distrust and precaution. The Ukrainian economy is particularly vulnerable due to constant instability. Instable situation is similarly observed not only in Ukraine but in other countries it is not ‘burdened’ with warfare and is a consequence of substituting the social-democratic model of the economy with the neoliberal one. Under the neoliberal model of the economy, the state loses the function of regulating the economy, and large corporations and enterprises are not obliged to provide their employees with social and economic guarantees. The social economic policy has no longer any signs of humanity, and respectively, the phenomenon of economic elasticity (flexibility) spreads, working conditions and attitudes to it modify. In the social space of modernity, a phenomenon of precarious social practices comes into being and rapidly spreads. They relate to the field of professional occupation, are characterized with a state of permanent uncertainty, insecurity of labor rights and instability of the labor market. They indirectly influence other areas of human life and functioning of the society. A new social stratum, the precariat, comes into being; it has not acquired attributes of a social class yet but it has already become a significant social force. In many respects, the precariat is similar to the proletariat, and therefore, in the presence of an appropriate ideology such as Marxism, it can become the driving force of new social revolutions. There is an actualized task to develop effective social mechanisms and measures in order to minimize the spread of precarious social practices. It is particularly important in the Ukrainian society which is characterized with uncertainty and insecurity of the political and economic course of the state. As a result, there is a significant migration activity of the able-bodied public which does not only pose a threat to the economic development of the state but is a significant social danger.